Pain affect disrupted in children with posterior cerebellar tumor resection. Issue 2 (2nd January 2019) - Silva, Katie E.; Rosner, Julie; Ullrich, Nicole J.; Chordas, Christine; Manley, Peter E.; Moulton, Eric A.
Abstract: Objectives: Damage to the posterior cerebellum can cause affective deficits in patients. In adults, cerebellar infarcts result in thermal hyperalgesia and affect descending modulation of pain. This study evaluated the effect of resection of low‐grade cerebellar tumors on pain processing in human children. Methods: Twelve pediatric patients treated with surgery only for low‐grade gliomas (8 females, 4 males; mean age = 13.8 ± 5.6) and twelve matched controls (8 females, 4 males; mean age = 13.8 ± 5.7) were evaluated using quantitative sensory testing and fMRI. Five patients had tumors localized to posterior cerebellar hemispheres, henceforth identified as Crus Patients. Results: Crus Patients had significantly lower pain tolerance to a cold pressor test than controls. No significant differences were detected between subject groups for heat and cold detection thresholds (HDT, CDT), and heat and cold pain thresholds (HPT, CPT). Crus Patients also showed significantly decreased fMRI responses to painful heat in anterior insula, which has been associated with pain affect. Interpretation: Damage to posterior cerebellar hemispheres disrupted affective pain processing and endogenous pain modulation, resulting in decreased pain tolerance to suprathreshold noxious stimuli. This suggests that surgical resection of this region in children may increase the risk of developing pain disorders.